PERBEDAAN DAYA TERIMA KONSUMEN TERHADAP EKSTRAK MAWAR (ROSA CENTIFOLIA) SEBAGAI PEWARNA ALAMI PADA PEMBUATAN LIPSTICK - Hidayah, Nurul (Jurnal Tata Rias, 2015)
Nurul Hidayah, (Difference in Consumer Acceptance on Rose Extract (Rosa Centifolia) asNatural Color for Lipstick) a qualitative study in Cosmetology Study Program, Faculty ofEngineering, Univercity Of Jakarta 2015This study aims to determine the most preferred lipstick cosmetics products by consumers inlipstick preparations that use natural dyes from rose extract 5%, 10%, and 15%. The samples usedin this study were 30 students of the State University of Jakarta who had dry lip conditions andevery day using lipstick. Assessment is carried out with a favorite / hedonic test. Aspects assessedare color, aroma, stickiness, and sensitivity. The results showed that there were differences in consumer acceptance of the results of color, aroma, adhesion, and sensitivity in lipstick preparationsusing natural dyes from rose extract 5%, 10%, and 15%. The results of the assessment stated that:the highest assessment of the color aspect obtained an average value of 3.93, namely in the lipstickpreparation using rose extract natural dyes 15%, this is because the colors in the lipstick preparationtend to be brighter and redder. The highest rating on the aroma aspect which has the highest averageof 4.70, that is, on lipstick that uses natural rose extract 15% because the smell is more smelled.While the assessment of the adhesion aspect obtained the highest value with an average of 4.70,namely in lipstick preparations using natural dyes from rose extract 15%. Finally, the assessment onthe sensitivity aspect obtained the highest average value of 4.33, that is, on lipstick preparationsusing natural dyes from rose extract 5%, this was due to the lipstick with a slight mixture of dyeswhich was the safest so it can be concluded that lipstick preparations using natural dyes from roseextract 15% more preferred by consumers ranging from color, aroma, and stickiness so that themore extracts used, the more attractive to consumers.